Ethical Issues in Online Course Design: Negotiating Identity, Privacy, and Ownership - Dich, Linh; McKee, Heidi A.; Porter, James E. (AoIR Selected Papers of Internet Research, 2013)
Ethical Issues in Online Course Design: Negotiating Identity, Privacy, and OwnershipThis panel will address several key ethical issues related to the design of online (or hybrid) courses and ways in which students and faculty may need to resist implicit or appropriate more explicit approaches toward Web technologies and communications. As faculty members move their traditional courses online, or as they design entirely new online or hybrid courses, new ethical issues certainly surface, particularly when students are asked to move from the privacy of the traditional classroom into the public realm of social media or when the university begins to rely on third-party services as platforms for course delivery (e.g., (Google+, Facebook, Udacity, Coursera).The three speakers on this panel will present their research on three distinct kinds of ethical issues that emerge when faculty take their students into online public spaces or when the courses themselves are taught online — issues related to identity (Speaker #1), privacy (Speaker #2), and ownership (Speaker #3). All three speakers are scholars and teachers in the field of rhetoric/composition whose research focuses primarily on rhetorical and ethical issues related to digital writing — but the issues to be discussed apply widely to all scholars doing research on, or developing, online courses or classroom spaces.The three of us proposing this panel certainly favor moving courses, faculty, and students online and into the public realm of social media, and we are by no means against third-party Web hosting arrangements. But our research shows that we need to be cautious and critical in our approach to such alignments. We have to be wary of how new technologies and applications, new social media spaces, and new institutional alignments can affect ethical relationships. The old rules don’t always apply, or not always in the same way. And the “new rules” are sometimes buried in inaccessible or incomprehensible terms of services — or simply remain implicit. Our research shows that we have to alert our students to the new rules and to their ethical implications — for instance, letting them know about potential hazards, as well as benefits, of posting online as a person of color; or letting them know the privacy implications involved in setting up a Facebook account or in clicking the “I Agree” button on a user license. At times our resistance has to take the form of proactive negotiation with our home universities — for instance, making sure that our universities do not develop policies or licensing arrangements that threaten students’ identities or rights.Speaker #1 will report on her 18-month ethnographic study of users in the social network site Xanga. She will examine academia’s understanding of “public writing,” pointing out that representations of public writing or “the online public” are often overly abstract, failing to account for particular community practices or the identities of particular community members. Specifically, she argues that scholarship has failed to examine how racial identities and writers function in the representation and construction of the public. Drawing on extensive interviews and observations with participants she will demonstrate how Asian-Americans produced and negotiated their identities through online language practices and provide recommendations for the design of more ethical online spaces that foster more equitable participation.Speaker #2 will report on privacy in online spaces like Facebook, Twitter, and Google+, in light of changes in technology practice (e.g., data mining) and privacy policies for social media. She will report on studies, including several she has conducted, that examine users’ perceptions of privacy. The implications of this research are that as scholars who often teach using online technologies we need to ensure we address privacy issues. She closes with ways that we can take research data and transform it for use in the design of online classes.Speaker #3 will report on his research on faculty ownership of online courses and course material. For this presentation he will consider the specific issue of faculty and student copyrights in MOOCs that are hosted by third parties outside the university. He will examine and critique several MOOC licenses on the grounds that they elide the distinction between course and course content, thereby undercutting the value of the university’s service and potentially damaging the university’s ethical relationship with students. Universities should avoid entering into MOOC licensing partnerships that treat the course as an object rather than as a social performance or that fail to provide adequate protection for faculty and students intellectual property.